Psychotherapeutic Implications of Psychic Dissonance on Gay Roman Catholic Diocesan Priests| A Phenomenological Study - Mascaro, John (Pacifica Graduate Institute, 2017)
Psychological research in the area of Roman Catholic priests has been extremely limited. The few studies that do exist have focused on emotional exhaustion, anxiety, and depression of religious and diocesan priests. With the sexual abuse scandals creating intense media scrutiny on gay Roman Catholic priests along with the population of priests declining each year and the number of Roman Catholics increasing, diocesan priests are expected to take on more responsibility for a greater number of parishioners. Recent studies have not looked at the effects of this current environment on gay Roman Catholic diocesan priests. This study focused on the psychotherapeutic implications of dissonance on Roman Catholic priests who self-identify as gay. A phenomenological approach was used in this study to understand the experience of dissonance on gay Roman Catholic diocesan priests. Ten participants were interviewed in depth about their experience. Participants’ responses were transcribed and descriptions were created to depict the life experience of each priest accurately. The interviews were analyzed and common themes were developed based on the experience of dissonance on Roman Catholic diocesan priests who self-identify as gay. The findings were looked at from a depth psychological perspective to examine the psychotherapeutic implications of psychic dissonance on gay diocesan priests working in active ministry within the Roman Catholic Church. The following seven themes were found to be common among the participants: (1) experiences support and self-care as an integral part of healthy functioning; (2) experiences conflict in reconciling personal values with Church teaching; (3) experiences discomfort and disruption (emotion, cognitive, and physical); (4) experiences development of gay identity as a healthy aspect of self; (5) experiences celibacy as difficult and for some gay priests, optional; (6) feels that discernment of personal experience takes precedence over Church teachings; (7) feels called to the work and ministry of priesthood. Each of these themes helped to create a better understanding of gay Roman Catholic diocesan priests and can be utilized as a template in working with them throughout the therapeutic process.